Comparative Evaluation of 99mTc-Pertechnetate, 99mTc-Diphosphonate, 99mTc-Solcocitran, 99mTc-Iron-Ascorbic Acid and 67Ga-Citrate as Brain Scanning Agents - Pétursson, E.; Björnsson, Ó. G.; Björnsson, O. J.; Davídsson, D. (Nuklearmedizin - NuclearMedicine, 1982)
The uptake of 99mTc-pertechnetate (TcO4), 99mTc-iron-ascorbic acid (Feasc), 99mTc-Solcocitran (Solcocitran), 99mTc-diphosphonate (HEDP) and 67Ga-citrate (Ga) in various brain lesions was compared. Influence of time from injection was also studied on the first three compounds. A rank correlation method was used to compare the scans which were judged visually by three independent observers. There was good agreement between the observers, as measured by Kendall’s τ, but the concordance between rankings within the same type of lesion, as measured by Kendall’s W, was rather poor. There was no significant difference in the uptake of TcO4, Feasc and Solcocitran. Ga showed generally poor uptake and its uptake in tumours and infarcts did not differ significantly. However, when HEDP and TcO4 were compared in two groups (I: Infarcts, haemorrhages and bone invading meningiomas, and II: Tumours not invaded into bone) a highly significant difference was obtained with much higher uptake of HEDP in Group I.